Evolution of Microexplosion Phenomenon in Parent-Child Droplets of Water in Biodiesel Emulsions Enhanced by Different Surfactant Dosages and Hydrophilic-Lipophilic Balance Values - Abdul Karim, Z.A. (American Society of Mechanical Engineers (ASME), 2019)
This experimental study endeavors to investigate the evolution of microexplosion phenomenon of water in biodiesel emulsion droplets with the base fuel (B5) containing 95 diesel and 5 of palm oil methyl ester (POME). Parameters such as water content varied from 9, 12, and 15, surfactant dosages of 5, 10, and 15 and the hydrophilic-lipophilic balance (HLB) values of 6, 7, 8, and 9 were varied to study its impact on microexplosion phenomenon. Three different sizes of emulsion droplets of approximately Ã2.8 mm, Ã2.2 mm, and Ã0.3 mm were visualized for the evolution of microexplosion phenomenon under the Leidenfrost effect using hot plate as a heat source. The evolution of microexplosion phenomenon of parent droplets, puffing behavior, and waiting time was visualized with high-resolution images. It was observed that the coalescence process was the dominating factor in inducing the microexplosion, and the coalescence process can either be advanced or be delayed by the surfactant dosage. The waiting time for the microexplosion was found to be influenced by the surfactant dosage and the droplet size. The rate of phase change of emulsions and puffing was found to be influenced by the surfactant dosage. By analyzing the postbehavior of the child droplets formed after the microexplosion of the parent droplet, it was observed that the child droplets undergo a series of puffing process and eventually microexplosion phenomenon also. The size of the parent droplets has a significant influence on the size of the child droplet. Â© 2019 by ASME.